Basic Life Support Training for Autonomous Organizations (Ortom) Muhammadiyah - Ida Rosidawati; Hana Aryani; Hisyam Farhan; Ihnatul Fauziah; Widy Andriana; Dera Trisna (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Emergency events certainly cannot be predicted, whenever and wherever someone can experience it, the event requires immediate help. Delays in handling can result in physical disability or even death. This condition requires proper and immediate emergency treatment, so that first aid in victims / patients can be done optimally. The role of the community in first aid to health problems has been widely felt and in general who find the first time emergency patients at the scene is a community known as